Influence of Leadership Style to Transfer Knowledge and Culture Organization to Improve Performance of Office Officer - Chairil Anwar; Syamsu Alam; Muhammad Asdar (Hasanuddin Journal of Business Strategy, 2020)
The purpose of this study was to determine and analyze the influence of leadership style, organizational culture on knowledge transfer, and employee performance. This research was conducted at the Boven Digoel Regent's office. The sample used in this study is the entire population or saturated samples as many as 90 respondents. The collection methods in this study were questionnaires and interviews. The data analysis method used path analysis with the Smart PLS application. The results showed that leadership style has no significant effect on knowledge transfer and employee performance. When mediated by knowledge transfer, the leadership style to affect employee performance was also insignificant. Organizational culture has a significant positive effect on knowledge transfer, but interestingly has no significant effect on employee performance. Organizational culture has a significant positive effect on employee performance if it is mediated by knowledge transfer. Transfer knowledge has a positive and significant effect on employee performance.